Pathways to independence: towards producing and using trustworthy evidence. (3rd December 2019) - Moynihan, Ray; Bero, Lisa; Hill, Sue; Johansson, Minna; Lexchin, Joel; Macdonald, Helen; Mintzes, Barbara; Pearson, Cynthia; Rodwin, Marc A; Stavdal, Anna; Stegenga, Jacob; Thombs, Brett D; et al.
Abstract : A global team of influential researchers, clinicians, regulators, and citizen advocates suggest how we can start to build an evidence base for healthcare that is free of commercial influences